Strategi Kepemimpinan Kepala Bagian Dalam Meningkatkan Kinerja Pegawai Pada Badan Amil Zakat Nasional Provinsi Jawa Timur: Laporan Kegiatan Kuliah Kerja Lapangan - Fairuz Fanisa Rahma; Bambang Karnain; Harsono Teguh S.; Rina Dewi (Jurnal Pengabdian Masyarakat, 2024)
Basically, employee performance is influenced by two factors, namely internal factors and external factors. Internal factors are factors related to a person's characteristics, including attitudes, personality traits, physical characteristics, desires or motivation, age, gender, education, work experience, cultural background and other personal variables. Meanwhile, external factors are factors that influence employee performance that come from the environment, leadership, actions of co-workers, type of training and supervision, wage system and social environment. Meanwhile, one of the important elements in a company's management system besides human resources is and compensation is leadership. Leadership is a process where someone can become a leader through continuous activities so that they can influence the people they lead (followers) in order to achieve organizational or company goals. The relationship between a leader and those being led is a leadership process because the leader needs followers and the followers need the leader. Even though leaders and followers are interrelated, it is the leader who should take the initiative to establish relationships, communicate and maintain relationships so that the goals of the company or organization as formulated in the company's/organization's vision, mission, plans and strategies can be achieved. Increasing employee performance in an organization is largely determined by the existence of leadership in the organization. Leadership is the main factor in determining the progress and decline of employee performance in an organization, because with leadership you can direct and mobilize other people to be willing. doing something voluntarily to achieve a predetermined goal. Therefore, the existence of leadership in an organization greatly determines the success of an organization as a whole. individual and group success